Karakteristik Pluralitas Agama di Aceh - Abd Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Basically, different types of diversity in all its forms are not something that happen because of a mistake of God. God is the One Almighty who may not do the slightest mistake. Then, can the mistake be transferred to other than God, such as the nature and human themselves? It is impossible to answer the question “yes.” Then another question we should ask is not who is mistaken for the occurrence of this diversity, but what is the wisdom behind the diversity itself. This article examines the understanding and the characteristic of the plurality of religions in Aceh. It is very important to be explored because Aceh has a mandate as a special area. The specificity includes the enactment of Islamic law and the implementation of governance set out in the Law on Governing Aceh.